The current practices of Islamic Build Operate Transfer (BOT) financing contracts: A legal analysis - Markom, Ruzian; Engku Ali, Engku Rabiah Adawiah; Hasan, Aznan (Universiti Pertanian Malaysia Press, 2012)
Build Operate Transfer (BOT) is a kind of legal mechanism of privatisation. It is a business venture between the government and the concessionaire, with the ownership of the project asset transferred to the government at the end of the concession period. In Malaysia, a decade after the beginning of privatisation was marked by the emergence of capital market which consisted of conventional and Islamic capital market. Both Islamic and conventional capital markets facilitate the privatisations and infrastructure projects by the issuance of bonds, equity financing securities and Islamic securities. Islamic BOT financing is a new type of contract in contemporary Islamic law, and it is resulted from the modern infrastructure development needs. Although the financing of BOT is new to the Islamic law, the specific contracts used in the structure are common to the Islamic principles of muamalat (i.e. Islamic transactions) like sale, partnership and lease contract. The objective of this work was to study the current practices of the Islamic BOT financing contracts in Malaysia and other countries. The study adopted an analytical approach by assessing the strengths and weaknesses of the financing contracts via the sale, partnership, and lease contract. Finally, the findings showed that sale-based financing is more popular to the Project Company of BOT in Malaysia due to the fixed return and deferred payment mechanism. On the other hand, the mudarabah and musharakah contract provides an alternative to the project since both structures are in the form of business venture and lease-based financing which exploit the beneficial interest of an asset.